Organizational Intelligence of the Academic Leaders at the University of Benghazi From the Point of View of Faulty Members (Abhat Journal, 2024)
the aim of the current research is to find out the level of or generational intelligence of the academic leaders at the university of Benghazi from the point of view of the faculty members the research community consisted of (2575) faculty members, while the sample consisted of (335) faculty members, the research used the questionnaire as a data collection tool, it was applied to (318) items for the purpose of statistical analysis the research used the (spss) statistical bag ,and the research concluded that the level of organizational intelligence among a academic leaders at the university of Benghazi from the point of view of faculty members was (1.70), which is an average level, there are also statistically significant differences between males and females for the dimensions (strategic vision, common destiny ) in favor of females, while there are no statistically significant differences for the dimensions (strategic vision ,desire to give , work pressures ) between applied and humanities faculties, in favor of applied colleges , while there are no differences attributed to the nature of the college variable for the rest of the dimensions , and there are no statistically significant differences between the sample member. Responses to the level of application of organizational intelligence among academic leaders at the university of Benghazi due to the years of experience variable  and that there are obstacles that prevent the application of the organizational intelligence university of Benghazi, the most important of which are stereotyped and poor use of communication and information technology means.
Keywords: Organizational intelligence of the academic leaders; faculty members; University of Benghazi